ANALISIS POLA PEMASARAN PRODUK HNI-HPAI DALAM MENINGKATKAN JUMLAH PENJUALAN DILIHAT DARI PERSPEKTIF BISNIS SYARIAH - Khairunnisa, Viona; Dewi, Sandra (Jurnal Ekonomi Sakti, 2024)
This thesis was prepared by Viona Khairunnisa NIM 3720037, Bachelor's Department of Sharia Business Management, Faculty of Economics and Islamic Business, UIN Sjech M. Djamil Djambek Bukittinggi with the title "Analysis of HNI-HPAI Product Marketing Patterns in Increasing the Number of Sales Viewed from a Sharia Business Perspective (Case Study Bukittinggi Business Center)”. This research is motivated by the marketing pattern of HNI-HPAI products using the PCA (Use, Tell, Invite) marketing system pattern to educate and encourage consumers to use HNI-HPAI products, still using traditional or formal methods, face to face, while other competing businesses have switching to an online marketing system such as product marketing through product content that is interesting and not boring so that it attracts a wider and larger target market. This research aims to analyze the marketing patterns for HNI-HPAI products used by BC HNI-HPAI Bukittinggi 2 in increasing sales from a sharia business perspective. A qualitative descriptive approach was used in this research. Observation, interview and documentary methods were used by researchers to collect data. Collecting data, cleaning it, presenting it, and drawing conclusions are the steps in data analysis. The research findings show that the HNI-HPAI product marketing model is reviewed from a sharia business perspective in order to increase sales at the HNI-HPAI Bukit Tinggi 2 Business Center. The model is then implemented appropriately. through the concept of sharia in business. As a result, this will greatly improve the long-term viability of BC HNI-HPAI Bukittinggi 2, as well as influence the loyalty and royalty choice of HNI-HPAI partners when purchasing HNI-HPAI goods. Keywords: Marketing Patterns; HNI-HPAI products; Sale; Sharia Business Perspective